The Hydrogeological investigation of Plajkoy spring (Elazig) - Okan, Ozlem Oztekin; Guven, Atahan; Cetindag, Bahattin (Maden Tetkik ve Arama Genel Mudurlugu-Mta, 2018)
Plajkoy spring discharges at the close locations to the SE shore of Lake Hazar. Lake Hazar is a tectonic Lake in Elazig city. Plajkoy spring is a fault spring that is mainly recharging from the volcanites, dikes and blocky volcanosedimentary units of Middle Eocene Maden Complex. These units have gained secondary permeability and porosity related with the active tectonics that is effective in the studied area. The present catchment system of the spring could not collect the springs and leaks discharging from different points around the system. The discharge of the catchment is measured by specific volume method while the other springs' and leaks' is measured by using triangular weir. Before the discharge measurement of the leaks and the springs, they have been directed to a channel. The discharge of the present catchment system and the leaks have measured twice in a month during one year period beginning from October of 2012 to November of 2013. The discharge coefficient of the spring is calculated 1.33*10(-3) day(-1). Discharge coefficient of the spring depends on the geometry and intensity of the active fracture systems in the region. Calculated discharge coefficient indicates that the spring discharge is related with the narrow fissures, fractures and pores. The total volume of discharged groundwater in the real regime of the Plajkoy spring is calculated as 52* 10(3) m(3) during the period from 31st of March, 2013 to the 13rd of October, 2013 by Maillet formula. The spring water is Ca- Mg- HCO, type water related with the chemical analyses. The chemical and microbiological analyses of the spring water are correlated with the drinking water standarts of Turkey TS 266 (TSE, 2005) and World Health Organization (2004), and it is seen that the spring water is suitable for drinking. The Plajkoy spring will be used more efficiently without exposed to pollution by the new catchment plan and protection zone map that are consequently proposed in the present study.
Plajköy kayna?inin (Elazi?) hidrojeoloji incelemesi